2023
DOI: 10.1111/jcpe.13770
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of teeth in patients susceptible to periodontitis: Clinical outcomes and risk factors associated with tooth loss after active therapy and 30 years of supportive periodontal care

Abstract: Aim (i) To evaluate the efficacy of active periodontal therapy supplemented by supportive periodontal care (SPC) in retaining dentition during a 30‐year follow‐up period in patients susceptible to periodontitis, and (ii) to assess the prognostic factors associated with tooth loss. Materials and Methods One‐hundred and fifty‐four patients with periodontitis, retrospectively classified as stage I–IV and grade B–C periodontitis, treated between 1984 and 1986 in a private practice, were enrolled in this study. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…reported that 5.6% of teeth were lost during SPT and 3.6% due to periodontitis over an average of 6 years in SPT, a higher incidence of TLP during periodontal maintenance was observed, namely 0.14 teeth/patient/year. The contrary was observed by Agudio et al 24 . over 30 years of follow‐up.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…reported that 5.6% of teeth were lost during SPT and 3.6% due to periodontitis over an average of 6 years in SPT, a higher incidence of TLP during periodontal maintenance was observed, namely 0.14 teeth/patient/year. The contrary was observed by Agudio et al 24 . over 30 years of follow‐up.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, even though Siow et al 6 reported that 5.6% of teeth were lost during SPT and 3.6% due to periodontitis over an average of 6 years in SPT, a higher incidence of TLP during periodontal maintenance was observed, namely 0.14 teeth/patient/year. The contrary was observed by Agudio et al 24 over 30 years of follow-up. Overall, 201 (5.1%) teeth were extracted during SPT, resulting in a total loss of 0.04 teeth/patient/year, of which only 39 (1%) were due to periodontal reasons, that is, 0.01 teeth/patient/year.…”
Section: (A) Variablesmentioning
confidence: 64%
“…Periodontal therapy aims to increase the longevity of natural teeth, emphasizing efforts to improve the probability of tooth survival [1]. Factors negatively influencing non-surgical periodontal treatment outcomes include smoking habits, supragingival plaque, and deep PD in molar teeth [6].…”
Section: Discussionmentioning
confidence: 99%
“…A tooth with an advanced periodontal lesion, i.e., severe bone loss, tooth mobility, class II or III furcation involvement, is considered a periodontally compromised tooth. Treating such teeth represents a clinical challenge because of their reduced chances of success [1]. When determining the prognosis, predictions regarding the disease course, duration, and outcomes are made based on general knowledge of disease pathogenesis, risk factors, and treatment options.…”
Section: Introductionmentioning
confidence: 99%